Comparação do diagnóstico sorológico da leishmaniose visceral canina entre laboratórios de Belo Horizonte, 2003 - 2004. - Juliana Giantomassi Machado (2004)
We evaluated five of the eight laboratories that perform serologic diagnosis of canine visceral leishmaniasis in Belo Horizonte, Minas Gerais. We analyzed the efficiency of the techniques of immunofluorescence assay (IFA) and indirect enzyme linked immunosorbent assay (ELISA) and the concordance between laboratories using 86 sera from dogs positive and 57 negative. The results showed that the sensitivity of indirect immunofluorescence and ELISA laboratories ranged from 98.8 to 100%. The specificity of immunofluorescence indreta a100 94.7% and the "enzyme linked immunosorbent assay" of 96.5 to 100%. These differences were not statistically seignificativas (p> 95%). The concordance between techniques in the same lab and they range from great to perfect according to the criteria of the Kappa test. The positive predictive value (PPV) and negative (NPV) were calculated according to the estimated prevalence of leishmaniasis, 2, 5, 8, 10 and 20% and the positive predictive value ranged from 27.95 to 100% and negative in 99.71 100% in the techniques of all laboratories evaluated. The positive samples showed a higher frequency in the titles of 1 / 320 to 1 / 1280. This study showed that there is a high concordance between laboratories in the identification of sera from dogs positive and negative for canine visceral leishmaniasis